Representation of the eastern and southeastern provinces in the Turkish Parliament during the national struggle and single-party era (1920-1946) - (:unkn) unknown (HOMER ACADEMIC PUBL HOUSE, 2011)
This article examines the socio-economic background of the parliamentary deputies serving during the years of the national struggle (19201922) and the single-party era (1923-1946) and provides new statistical data collated from recently published, detailed biographical information. I will provide a critical analysis of the socio-economic background of the deputies elected to represent the eastern and southeastern regions of Turkey and offer localism defined as being born in the and from the constituency one represents as a key concept to allow a better understanding of the nature of the electoral process at that time. Although localism which can be regarded as one of the important indicators of authentic representation was extensive during the years of the national struggle, it was replaced by bureaucratic representation during the single-party era, especially starting with the 1927 elections held right after the Sheikh Salt Rebellion. The article relates the Kurdish rebellions to the problem of representation in parliament and shows that in the rebellions' aftermath the number of the local representatives rapidly decreased. It further documents that, with the introduction of multi-party politics and democratic, free, competitive elections after the World War II, a return to localism can be observed for the eastern and southeastern provinces of Turkey.
Keywords: Single-party era; Kurdish parliamentary representation; Turkish elections; localism; Turkish Grand National Assembly